Kingdom of the Netherlands-Netherlands : Publication of Financial Sector Assessment Program Documentation: Technical Note on Pensions Sector Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The recent crisis and interest rate declines have put the financial sustainability of the Dutch occupational pension system under severe strain. The benefit-cutting measures have been received by the public as an unexpected and almost unknown option inherent in the pension contracts. Adding to the strain on the pension funds is an unexpected increment in the longevity of the Dutch population. The transparency and risk-sensitive framework of pension funds regulation has brought the question of the sustainability of the Dutch pension system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet